The enhancement of growth and yield of oyster mushrooms (Pleurotus pulmonarius) on cassava peels and stalk using vitamins - Akinrinola-Akinyemi, A O; Onawola, O O; Asagbra, A E; Ashiru, W B; Sanni, L O; Dike, E N (Mushroom Research, 2019)
The use of vitamins as enhancements in the cultivation of mushroom is to serve as a booster to the wastes which do not contain organic nutrient. The result of vitamin addition as supplement for the enhancement of growth showed a significant improvement in the rate of colonization which was reduced from 9 days in non-supplemented substrates to 4 days in substrates that were supplemented with vitamins. The primordial appearance also observed to be positively affected as healthy primordial that fruited to maturity were recorded in supplemented substrates; this was the case in non-supplemented substrates which recorded higher number of 29 primordial heads while 3-4heads will mature to fruit bodies. The flush phase was observed to be reduced from 10-12 days to 5-6 days, a 50% enhancement in production. Cobalamine gave the highest harvest both in cassava peels and stalk 88.5, 86.4 and 83,3g in cassava peels and 129.5g, 125.9g and 120.5g in cassava stalk. Substrates A1, A2 and A3 in tables 1 and 2 had combined vitamins in different proportion of riboflavin 3ml, cobalamine 1ml and folic acid 1ml in A1, A2 had a proportion of riboflavin1ml, cobalamine 3ml and folic acid 1ml while A3 had riboflavin 1ml, cobalamine 1ml and folic acid 3ml. The fruiting from these substrates showed that substrates A2 with 3ml of cobalamine had a yield of 94.6g in table 1 and 78.3g in table 2. High concentration of vitamins on the substrates enhanced colonization days, primordial appearance days and the fruiting pattern.